Towards a Quantitative Description of Proteolysis: Contribution of Demasking and Hydrolysis Steps to Proteolysis Kinetics of Milk Proteins - Mikhail M. Vorob’ev (Foods)
The hydrolysis of proteins by proteases (proteolysis) plays a significant role in biology and food science. Despite the importance of proteolysis, a universal quantitative model of this phenomenon has not yet been created. This review considers approaches to modeling proteolysis in a batch reactor that take into account differences in the hydrolysis of the individual peptide bonds, as well as the limited accessibility (masking) for the enzymes of some hydrolysis sites in the protein substrate. Kinetic studies of the proteolysis of β-casein and β-lactoglobulin by various proteolytic enzymes throughout the whole degree of hydrolysis are reviewed. The two-step proteolysis model is regarded, which includes demasking of peptide bonds as a result of opening of the protein structure at the first stage, then hydrolysis of the demasked peptide bonds. To determine the kinetics of demasking, the shift in Trp fluorescence during opening of the protein substrate is analyzed. Two stages of demasking and secondary masking are also considered, explaining the appearance of unhydrolyzed peptide bonds at the end of proteolysis with decreasing enzyme concentrations. Proteolysis of a nanosized substrate is considered for the example of tryptic hydrolysis of β-CN micelles, leading to the formation and degradation of new nanoparticles and non-monotonic changes in the secondary protein structures during proteolysis.